Arterial Hypertension in Children - Rascher, Wolfgang; Paech, Christian (Pediatric Pharmacotherapy, 2020)
Pharmacological treatment of arterial hypertension in children is mainly based on individual experience, but there is evidence that blocking the angiotensin system reduces systolic and diastolic blood when compared to placebo, and these drugs are safe to use for a short duration, also in children under 6 years of age. Blocking the angiotensin system either by angiotensin-converting enzyme inhibitors or by antagonizing the angiotensin 1 receptor is effective, but did not display a consistent dose-response relationship with escalating doses, but the effective doses are known. Calcium channel antagonists are effective antihypertensives in children, but the evidence is limited. Based on small-sized studies, beta-blockers modestly reduce systolic blood pressure, but have no significant effect on diastolic blood pressure compared to placebo. They act in combination to antagonize reflex tachycardia induced by vasodilators. The most commonly used antihypertensive agents are safe to use in short-term studies.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Antihypertensives; Arterial hypertension; Clinical trials; Pediatrics